A Compulsion to Language in Psychoanalysis? - João José R. L. de Almeida (Critical Hermeneutics)
Can Wittgenstein’s philosophical method illuminate our understanding of psychoanalysis? This article argues yes, by analyzing Lacan’s ‘Science and Truth’. Focusing on Lacan’s structuralist concept of the subject, shaped by language and desire, the article highlights how a Wittgensteinian lens offers insights for a global assessment of what we do by applying psychoanalytic concepts.